Solve for m 11+3(m+3)=2

Math
11+3(m+3)=2
Simplify 11+3(m+3).
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
11+3m+3⋅3=2
Multiply 3 by 3.
11+3m+9=2
11+3m+9=2
Add 11 and 9.
3m+20=2
3m+20=2
Move all terms not containing m to the right side of the equation.
Tap for more steps…
Subtract 20 from both sides of the equation.
3m=2-20
Subtract 20 from 2.
3m=-18
3m=-18
Divide each term by 3 and simplify.
Tap for more steps…
Divide each term in 3m=-18 by 3.
3m3=-183
Cancel the common factor of 3.
Tap for more steps…
Cancel the common factor.
3m3=-183
Divide m by 1.
m=-183
m=-183
Divide -18 by 3.
m=-6
m=-6
Solve for m 11+3(m+3)=2

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top